Manajemen Komunikasi Krisis JKT48 Operation Team Pasca Kasus No Encore pada Konser JKT48 Full House 2025 - Utami Nur Azizah; Ridma Meltareza (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
This study examines the crisis communication strategies of the JKT48 Operational Team (JOT) following the 2025 “No Encore” incident, which emerged after the viral circulation of an inappropriate photo involving the group’s General Manager and escalated into a major reputational crisis. The controversy triggered strong fan backlash and culminated in the symbolic withdrawal of support during the Full House 2025 concert. Using a qualitative case study approach, this research analyzes organizational responses through interviews with fans, observations of social media interactions, and documentation of official statements. Data were interpreted using thematic analysis and compared with the principles of the Situational Crisis Communication Theory (SCCT). The findings show that JOT’s initial clarification was perceived as slow and insufficient, contributing to heightened dissatisfaction and crisis escalation. However, the second clarification and the introduction of FanSpace, a structured two-way dialogue forum, marked a shift toward more transparent and participatory communication. Fan responses indicate that FanSpace helped reduce tensions and demonstrated managerial willingness to listen, though full trust recovery requires consistent follow-up actions. This study highlights the importance of speed, openness, and dialogic engagement in crisis communication within fan-based entertainment industries. The implications emphasize that organizations must adopt adaptive, audience-centered communication strategies to rebuild legitimacy and restore public trust after preventable crises.